The Symbolism of Love in the Story of Panji Asmarabangun and Galuh Candrakirana as a Cultural Identity of Kediri: A Textual Study and Interpretation - Wiratama, Nara Setya; Budiono, Heru; Budianto, Agus; Afandi, Zainal; Widiatmoko, Sigit; Yatmin; Sasmita, Gusti Garnis; Rahmadhani, Sheva (International Journal of Contemporary Sciences (IJCS), 2024)
This study aims to reveal the symbolism of love in the story of Panji Asmarabangun and Galuh Candrakirana as a cultural identity of Kediri and its contribution to understanding local cultural values. Using a descriptive qualitative research method with a textual study and semiotic interpretation approach, this study analyzes Panji manuscripts from the Javanese classical period, collected over a three-month period. The results show that the symbolism of love in the Panji story represents values of loyalty, sacrifice, and harmony, reflecting the life philosophy of the Kediri community. The interpretation of these symbols strengthens the position of the Panji story as a cultural heritage that plays an essential role in shaping the cultural identity and moral values of Javanese society.